Development of a Decision-Making Approach for Mass Deworming Campaigns on Intestinal Parasites among Primary School Children in Egypt - Hassan, Noha Salah Abdelsamie; Radwan, Ghada Nasr (Open Access Macedonian Journal of Medical Sciences, 2021)
Intestinal parasitic infections are widespread and cause considerable morbidity. Although mortality from such infections is low, most intestinal parasitic infections interfere with nutrition, growth, development and cognitive progress of children, in addition to interference with productivity and quality of life of adults. Study Aim: Reduction of intestinal parasites prevalence among primary school children. Methods: this is a three-phased study; Desk review on current prevention and control methods including mass deworming in the light of global guidelines. Cross-sectional field study on 522 school children from 8 Governorates, and interviews with 168 members of the health team running the deworming campaign at these Governorates in 2017. Development of decision making approach to guide future consideration of mass deworming campaigns Results: National mass deworming campaigns were effective in reducing prevalence of intestinal worms among primary school children in Egypt, and provided a nationwide awareness on the issue. However, unless these campaigns are combined with sustainable measures of clean drinking water, sewage disposal in schools and households the success of these campaigns in reducing intestinal worms' prevalence will be transient. Conclusion and Recommendations: The national mass deworming campaigns ranged an alarm bell in the community about dangers of intestinal parasites. However, it's recommended to include other susceptible groups like preschool children, adolescent girls and women of childbearing age while focusing the deworming only on infected individuals. It's also recommended to convert the deworming campaigns into a program to ensure sustainability of resources and continuous monitoring and evaluation of intestinal parasitic burden among populations at risk. Key Words: Intestinal Parasites – Primary School Children – Mass Deworming Campaigns – Egypt